Creativity in the Design Process Exploring the Influences of the Digital Evolution - Bruno, Carmen; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
The book provides an open and integrated view of creativity in the 21st century, merging theories and case studies from design, psychology, sociology, computer science and human-computer interaction, while benefitting from a continuous dialogue within a network of experts in these fields. An exploratory journey guides the reader through the major social, human, and technological changes that influence human creative abilities, highlighting the fundamental factors that need to be stimulated for creative empowerment in the digital era. The book reflects on why and how design practice and design research should explore digital creativity, and promote the empowerment of creativity, presenting two flexible tools specifically developed to observe the influences on multiple level of human creativity in the digital transition, and understand their positive and negative effect on the creative design process. An overview of the main influences and opportunities collected by adopting the two tools are presented with guidelines to design actions to empower the process for innovation.
Adapting to a changed world -- Design exploring Digital Creativity -- Design Contribution: tools to observe and empower Creativity in the Digital Age.
Keywords: Technological innovations; Educational technology; Industrial design; Innovation and Technology Management; Digital Education and Educational Technology; Industrial Design; Creative ability; Design -- Philosophy